An emi shielding wave-absorbing material, a preparation method and application thereof

CN122958705APending Publication Date: 2026-10-23ANHUI MINGXUN NEW MATERIAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411609509.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]然而,在大多数这些复合材料中,需要高含量的导电料,这是由于在形成期填料聚集的可能性会引起较差的机械和加工性质,或可以使用较低含量的导电填料,但其导电性受到严重影响

Benefits of technology

[0017]在本发明中,采用铁钴合金纳米粒子作为所述EMI屏蔽吸波材料的关键组分,在制备过程中,使其随机地分散,形成一个低密度的合金纳米层,然后利用介孔氧化态的晶须结构,将铁钴合金纳米粒子承载起来,形成支撑层,加上烯基硅氧烷水解缩合形成的聚合物薄膜,所述EMI屏蔽材料的层次明显。而且,铁钴合金纳米粒子在经过真空高温退火后,粒子之间出现了焊接现象,这样的一种焊接网络能够有效降低接触电阻。从而,所得EMI屏蔽吸波材料的电磁屏蔽性和结构稳定性得到极大的改善。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides an EMI shielding wave-absorbing material and a preparation method and application thereof. The EMI shielding wave-absorbing material comprises iron-cobalt alloy nanoparticles, mesoporous titanium oxide and alkenyl siloxane. In application, the material is coated on the surface of a PET substrate to form a flexible film containing an adhesive and a release film. The porous structure of the mesoporous titanium oxide and the polymer film layer formed by the hydrolysis and condensation of the alkenyl siloxane, together with the welding points formed by the iron-cobalt nano-alloy particles after high-temperature annealing treatment, can not only improve the electromagnetic shielding capacity of the iron-cobalt nano-alloy particles, but also greatly improve the structural stability of the obtained conductive alloy layer, so that the conductive alloy layer can withstand the damage of salt spray and a damp-heat environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of materials, and more particularly to an EMI shielding and absorbing material, its preparation method, and its application. Background Technology

[0002] Electromagnetic interference (EMI) is an environmental pollution caused by natural phenomena (such as solar flares and electrostatic discharge) or electronic equipment. Natural electromagnetic pollution typically refers to electromagnetic radiation caused by natural phenomena such as atmospheric lightning, cosmic rays, and thermal radiation from the Earth and the Sun. Electromagnetic radiation caused by natural phenomena severely interferes with the normal operation of shortwave communication equipment. The use of electronic equipment is a widespread human need. The use of wireless devices, faster data services, mobile phones, and other communication devices that emit high-frequency electromagnetic radiation is gradually increasing. In the military, high-frequency signals are required to operate communication systems, control equipment, and radar sensors, and these signals can cause interference or malfunctions to adjacent equipment or devices. In daily life, EMI radiation affects many areas of daily life, including personal mobile phones, communications, and banking security, and may pose health risks with long-term exposure.

[0003] Traditionally, EMI shielding technology has primarily employed metal plates made of steel, copper, nickel, or aluminum alloys due to their high conductivity and dielectric constant. While these materials offer good EMI shielding performance, their high density, large size, high cost, narrow absorption band, susceptibility to corrosion, and poor regeneration capabilities limit their application in lightweight electronic devices and absorbing materials. Metal coatings, such as electroplating, electroless plating, spraying, and vacuum coating, have also been used for EMI shielding, but their poor abrasion resistance and environmental resistance, along with their primarily reflection-based shielding, render them unsuitable for practical applications. Alloys were once considered EMI shielding materials due to their relatively high permeability and light weight. However, their high hardness, corrosiveness, and high cost limit their practical application.

[0004] Therefore, researchers are dedicated to finding alternative solutions. In recent years, due to the advantages of polymer materials such as light weight, low price, good processability, and corrosion resistance, the development of high-performance polymer-based EMI shielding materials has attracted great interest from the scientific and industrial communities. However, apart from a few intrinsically conductive polymers, such as polyaniline, polypyrrole, and polythiophene, most polymers, such as epoxy resin, polystyrene, polyvinyl alcohol, and polyvinylidene fluoride, have insulating properties. To enable polymer materials to have good electromagnetic wave reflection and loss capabilities, polymer-based composite materials with conductive and magnetic fillers have become the optimal choice. These materials combine the advantages of polymers with those of conductive fillers (mainly to increase the dielectric constant of the polymer-based material) and magnetic fillers (mainly to increase the magnetic permeability of the polymer-based composite material) in one material. At the same time, it also maintains a good balance between mechanical properties and thermal stability.

[0005] However, most of these composite materials require a high content of conductive filler because the potential for filler aggregation during the formation period can lead to poor mechanical and processing properties. Alternatively, a lower content of conductive filler can be used, but its conductivity is severely affected. Moreover, most polymer composites containing conductive fillers suffer from problems such as low thermal conductivity, poor heat resistance, poor weather resistance, and excessive thickness.

[0006] Therefore, there is a need for an ultra-thin and flexible EMI shielding and absorbing material that not only has excellent EMI shielding performance but also excellent salt spray resistance, making it suitable for various smart electronic products. Summary of the Invention

[0007] To address some of the problems existing in the prior art, this invention provides an EMI shielding absorbing material, its preparation method, and its application.

[0008] An EMI shielding and absorbing material, by weight percentage, comprises the following raw materials: 10-35% iron-cobalt nano-alloy particles, 23.5-40% mesoporous titanium dioxide and 30-66.5% alkenylsiloxane.

[0009] In some embodiments of the present invention, the preparation process of the iron-cobalt nano-alloy particles includes the following steps: ferrous sulfate heptahydrate and cobalt chloride hexahydrate are prepared into aqueous solutions, the two solutions are added and mixed evenly under continuous stirring, oleic acid is added, and then the mixture is placed in a water bath at 30-40°C. A mixed solution of NaBH4 and potassium hydroxide is added dropwise, the mixture is stirred and reacted, and after precipitation is formed, the mixture is stirred and aged for 1-2 hours. After the product is filtered, washed, and vacuum dried, the iron-cobalt nano-alloy particles are obtained.

[0010] Furthermore, the mass concentration of the aqueous solution of ferrous sulfate heptahydrate is 27.8-83.4 g / L; and the mass concentration of the aqueous solution of cobalt chloride hexahydrate is 35.7-52.4 g / L.

[0011] Furthermore, the volume ratio of the aqueous solution of ferrous sulfate heptahydrate to the aqueous solution of cobalt chloride hexahydrate is 1:0.2-0.7.

[0012] Furthermore, in the mixed solution of NaBH4 and potassium hydroxide, the mass concentration of NaBH4 is 3.8-7.5 g / L, and the mass concentration of potassium hydroxide is 0.6-1.0 g / L.

[0013] In some embodiments of the present invention, the preparation process of the mesoporous titanium oxide includes the following steps: hydrated titanium oxide and potassium carbonate are dissolved in water at a molar ratio of 2:1-1.3 to form a non-flowing slurry, which is coated onto a thin ceramic sheet and dried. Then, the slurry is heated to 800-900°C in a muffle furnace, held at that temperature for 2-3 hours, and slowly cooled to room temperature. The resulting whiskers are ultrasonically dispersed in distilled water, filtered, and dried. Distilled water is added again to keep the mixture moist, and the mixture is allowed to stand at room temperature for 7 days. The mixture is then stirred in 1 mol / L hydrochloric acid, filtered, washed, and dried. The resulting crystals are placed in a muffle furnace and heat-treated at 300-500°C to obtain the mesoporous titanium oxide.

[0014] In some embodiments of the present invention, the alkenylsiloxane is at least one of allyltrimethoxysilane, 3-methyl-allyltrimethoxysilane, bis(trimethoxysilylmethyl)ethylene, 1,4-trimethoxysilyl-2,3-butene, allyltriethoxysilane, 2-methyl-allyltripropoxysilane, 3-methyl-allyltripropoxysilane (CAS: 84859-54-1), 2-methyl-2-enylbutyryltripropoxysilane (CAS: 35754-76-8), allyltripropoxysilane (CAS: 25079-67-8), 2-enylbutyryltrimethoxysilane (CAS: 13436-83-4), and 2-enylbutyryltriethoxysilane (CAS: 52111-26-9).

[0015] The method for preparing the EMI shielding and absorbing material includes the following steps: S1: The iron-cobalt nano-alloy is dispersed in ethanol and diluted with dichloromethane, then cast onto a glass plate. After evaporation and drying, a glass plate containing an iron-cobalt nano-alloy layer is formed. S2: Mesoporous titanium dioxide and alkenyl siloxane are completely dispersed in THF to obtain a mixed solution with a mass fraction of 15-16 wt%. This solution is poured into a petri dish containing an iron-cobalt nano-alloy layer obtained in S1, allowing the mixed solution to penetrate into the iron-cobalt nano-alloy layer mesh. Then, 1 mol / L hydrochloric acid solution is added dropwise, and the mixture is heated at 40-50℃ for 3-5 hours. After rinsing and drying, the film is peeled off from the glass plate and placed in a vacuum oven at 150℃ for high-temperature annealing for 1-2 hours to obtain the EMI shielding and absorbing material.

[0016] Furthermore, the mass ratio of the mesoporous titanium dioxide and alkenylsiloxane in S2 is 0.5-0.8:1.

[0017] In this invention, iron-cobalt alloy nanoparticles are used as the key component of the EMI shielding and absorbing material. During the preparation process, they are randomly dispersed to form a low-density alloy nanolayer. Then, the iron-cobalt alloy nanoparticles are supported by a mesoporous oxidized whisker structure to form a support layer. Combined with a polymer film formed by the hydrolysis and condensation of alkenyl siloxanes, the EMI shielding material exhibits distinct layers. Furthermore, after vacuum high-temperature annealing, the iron-cobalt alloy nanoparticles exhibit a welding phenomenon between the particles, and this welded network effectively reduces contact resistance. Therefore, the electromagnetic shielding performance and structural stability of the resulting EMI shielding and absorbing material are greatly improved.

[0018] However, excessive addition of mesoporous titanium dioxide leads to poor film formation and weak connectivity of the conductive network, making it difficult to form a good structure and thus affecting the conductivity and microwave absorption properties of the material. Therefore, preferably, the mass ratio of the mesoporous titanium dioxide to alkenylsiloxane is controlled at 0.5-0.8:1.

[0019] In the application of the EMI shielding and absorbing material described above, when preparing the EMI shielding and absorbing material, the glass plate is replaced with a PET film, and a release film can be bonded to the other side of the PET film with an adhesive.

[0020] Beneficial effects: Compared with existing technologies, this invention uses iron-cobalt alloy nanoparticles, mesoporous titanium dioxide, and alkenylsiloxane to prepare EMI shielding and absorbing materials. 1. By utilizing the whisker morphology of mesoporous titanium dioxide, low-density iron-cobalt alloy nanoparticles can be linked together to improve the conductivity of the iron-cobalt alloy nanoparticle layer; in addition, the porous structure of mesoporous titanium dioxide can improve the wave absorption of the material. 2. The hydrolytic polymerization of alkenyl siloxanes synergistically enhances the conductivity of the material on the one hand, and improves its structural stability on the other. More importantly, the film formed by the polymerization of alkenyl siloxanes greatly improves the material's salt spray resistance. 3. After high-temperature annealing, iron-cobalt alloy nanoparticles form welding points, which not only improve the electromagnetic shielding ability of the material, but also synergistically improve the structural stability of the material with alkenylsiloxane, enabling it to withstand humid and hot environments. Detailed Implementation

[0021] The present invention will be described below with reference to specific embodiments. It should be noted that the following embodiments are examples of the present invention and are used only to illustrate the invention, not to limit it. Other combinations and various modifications within the scope of the present invention can be made without departing from its spirit or scope.

[0022] The preparation process of mesoporous titanium dioxide used in the following embodiments is illustrated by way of example: Hydrated titanium dioxide and potassium carbonate were dissolved in water at a molar ratio of 2:1 to form a non-flowing slurry. This slurry was coated onto a thin ceramic sheet and dried. The sheet was then heated to 800°C in a muffle furnace and held at that temperature for 3 hours, followed by slow cooling to room temperature. The resulting whiskers were ultrasonically dispersed in distilled water, filtered, and dried. Distilled water was added again to keep the mixture moist, and the mixture was allowed to stand at room temperature for 7 days. The mixture was then stirred in 1 mol / L hydrochloric acid, filtered, washed, and dried. The resulting crystals were then heat-treated in a muffle furnace at 300°C for 2 hours to obtain the mesoporous titanium dioxide.

[0023] In addition, in the following embodiments, after the PET film is loaded with the EMI shielding and absorbing material, a release film is provided on the other side, and the two are bonded together by an adhesive.

[0024] Example 1 An EMI shielding and absorbing material comprises the following raw materials: 10% iron-cobalt alloy nanoparticles, 23.5% mesoporous titanium dioxide, and 66.5% allyltrimethoxysilane.

[0025] The preparation process is as follows: S1: The iron-cobalt alloy nanoparticles are dispersed in ethanol and diluted with dichloromethane, then cast onto a PET film. After evaporation and drying, a glass plate containing an iron-cobalt nano-alloy layer is formed. S2: Mesoporous titanium dioxide and allyltrimethoxysilane are completely dispersed in THF to obtain a mixed solution with a mass fraction of 15 wt%. This solution is then poured into a petri dish containing a PET film with an iron-cobalt nano-alloy layer obtained in S1, allowing the mixed solution to penetrate into the iron-cobalt nano-alloy layer mesh. A 1 mol / L hydrochloric acid solution is then added dropwise, and the mixture is heated at 40°C for 5 hours. After rinsing and drying, the dried film is placed in a vacuum oven at 150°C for high-temperature annealing for 1 hour to obtain the EMI shielding and absorbing material.

[0026] The preparation process of the iron-cobalt alloy nanoparticles is as follows: 27.8 g / L ferrous sulfate heptahydrate and 35.7 g / L cobalt chloride hexahydrate are prepared into aqueous solutions. The two solutions are mixed evenly under constant stirring at a volume ratio of 1:0.7. Oleic acid is added as a dispersant. Then, under a water bath at 30°C, a mixed solution containing 3.8 g / L NaBH4 and 0.6 g / L potassium hydroxide is added dropwise. The mixture is stirred and reacted until a precipitate is formed. After stirring and aging for 1 hour, the product is filtered, washed, and vacuum dried to obtain the iron-cobalt alloy nanoparticles.

[0027] Example 2 An EMI shielding and absorbing material comprising the following raw materials: 20% iron-cobalt alloy nanoparticles, 30% mesoporous titanium dioxide, and 50% bis(trimethoxysilylmethyl)ethylene.

[0028] The preparation process is as follows: S1: The iron-cobalt alloy nanoparticles are dispersed in ethanol and diluted with dichloromethane, then cast onto a PET film. After evaporation and drying, a glass plate containing an iron-cobalt nano-alloy layer is formed. S2: Mesoporous titanium dioxide and bis(trimethoxysilylmethyl)ethylene are completely dispersed in THF to obtain a mixed solution with a mass fraction of 15.5 wt%. This solution is poured into a petri dish containing a PET film with an iron-cobalt nanoalloy layer obtained in S1, allowing the mixed solution to penetrate into the iron-cobalt nanoalloy layer mesh. Then, a 1 mol / L hydrochloric acid solution is added dropwise, and the mixture is heated at 45°C for 4 hours. After rinsing and drying, the dried film is placed in a vacuum oven at 150°C for high-temperature annealing for 1.5 hours to obtain the EMI shielding and absorbing material.

[0029] The preparation process of the iron-cobalt alloy nanoparticles is as follows: 55.6 g / L ferrous sulfate heptahydrate and 43.5 g / L cobalt chloride hexahydrate are prepared into aqueous solutions. The two solutions are mixed evenly with constant stirring at a volume ratio of 1:0.5. Oleic acid is added as a dispersant. Then, under the condition of a water bath at 35°C, a mixed solution containing 5.2 g / L NaBH4 and 0.8 g / L potassium hydroxide is added dropwise. The mixture is stirred and reacted until a precipitate is formed. After stirring and aging for 1.5 h, the product is filtered, washed, and vacuum dried to obtain the iron-cobalt alloy nanoparticles.

[0030] Example 3 Similar to Example 2, except that the raw material composition is: 32.5% iron-cobalt alloy nanoparticles, 30% mesoporous titanium dioxide and 37.5% bis(trimethoxysilylmethyl)ethylene.

[0031] Example 4 An EMI shielding and absorbing material comprises the following raw materials: 30% iron-cobalt alloy nanoparticles, 35% mesoporous titanium dioxide, and 35% 2-methyl-2-enyltripropoxysilane.

[0032] The preparation process is as follows: S1: The iron-cobalt alloy nanoparticles are dispersed in ethanol and diluted with dichloromethane, then cast onto a PET film. After evaporation and drying, a glass plate containing an iron-cobalt nano-alloy layer is formed. S2: Mesoporous titanium dioxide and allyltrimethoxysilane are completely dispersed in THF to obtain a mixed solution with a mass fraction of 16 wt%. This solution is poured into a petri dish containing a PET film with an iron-cobalt nano-alloy layer obtained in S1, allowing the mixed solution to penetrate into the iron-cobalt nano-alloy layer mesh. Then, a 1 mol / L hydrochloric acid solution is added dropwise, and the mixture is heated at 50°C for 3 hours. After rinsing and drying, the dried film is placed in a vacuum oven at 150°C for high-temperature annealing for 2 hours to obtain the EMI shielding and absorbing material.

[0033] The preparation process of the iron-cobalt alloy nanoparticles is as follows: 83.4 g / L ferrous sulfate heptahydrate and 52.4 g / L cobalt chloride hexahydrate are prepared into aqueous solutions. The two solutions are mixed evenly with constant stirring at a volume ratio of 1:0.2. Oleic acid is added as a dispersant. Then, under the condition of a water bath at 40°C, a mixed solution containing 7.5 g / L NaBH4 and 1.0 g / L potassium hydroxide is added dropwise. The mixture is stirred and reacted until a precipitate is formed. After stirring and aging for 2 hours, the product is filtered, washed, and vacuum dried to obtain the iron-cobalt alloy nanoparticles.

[0034] Example 5 Same as Example 4, except that high-temperature annealing is not performed during preparation.

[0035] Comparative Example 1 Same as Example 4, except that mesoporous titanium dioxide is not added.

[0036] Comparative Example 2 Same as Example 4, except that 2-methyl-2-enbutyltripropoxysilane is not added.

[0037] Performance testing EMI attenuation rate: The EMI attenuation rate of the material at 50MHz, 1GHz and 3GHz was tested using an SSA3000X spectrum analyzer; Salt spray resistance: Refer to GB / T 646-2002 "Rating of specimens and test pieces of metal and other inorganic coatings on metal substrates after corrosion test" to calculate the corrosion resistance area of ​​the material in salt spray. Moist heat resistance: Tested according to GB / T 1740-2007 "Determination of Moist Heat Resistance of Coating Film".

[0038] The test results are detailed in Table 1: Table 1 Performance test results of the microwave absorbing materials obtained in Examples 1-5 and Comparative Examples 1-2 As can be seen from Table 1, Embodiments 1-5 of this application exhibit excellent wave absorption and shielding performance under different frequency operating environments. Furthermore, the materials have good resistance to salt spray and damp heat, enabling them to be used in harsh environments without rapid failure.

[0039] However, in Example 5, because the material was not subjected to high-temperature annealing, the internal conductivity of the absorbing component in the material was somewhat lacking. However, the alkenyl structure in the siloxane polymer could compensate for this to a certain extent, so that the electromagnetic shielding performance of the prepared EMI shielding absorbing material would not be lost too much.

[0040] The results of Comparative Examples 1-2 show that the addition of alkenylsiloxane plays an important role in improving the salt spray resistance and damp heat resistance of the material, and the lack of mesoporous titanium dioxide not only affects the electromagnetic shielding performance of the material, but also has a negative impact on the salt spray resistance and damp heat resistance of the material.

[0041] The above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.

Claims

1. An EMI shielding and absorbing material, characterized in that, By weight percentage, it contains the following raw materials: 10-35% iron-cobalt alloy nanoparticles, 23.5-40% mesoporous titanium dioxide and 30-66.5% alkenylsiloxane.

2. The EMI shielding and absorbing material according to claim 1, characterized in that, The preparation process of the iron-cobalt alloy nanoparticles includes the following steps: ferrous sulfate heptahydrate and cobalt chloride hexahydrate are prepared into aqueous solutions, the two solutions are mixed evenly under constant stirring, oleic acid is added, and then the mixture is placed in a water bath at 30-40℃. A mixed solution of NaBH4 and potassium hydroxide is added dropwise, and the mixture is stirred to react. After the precipitate is formed, the mixture is stirred and aged for 1-2 hours. The product is then filtered, washed, and vacuum dried to obtain the iron-cobalt alloy nanoparticles.

3. The EMI shielding and absorbing material according to claim 2, characterized in that, The aqueous solution of ferrous sulfate heptahydrate has a mass concentration of 27.8-83.4 g / L; the aqueous solution of cobalt chloride hexahydrate has a mass concentration of 35.7-52.4 g / L.

4. The EMI shielding and absorbing material according to claim 3, characterized in that, The volume ratio of the aqueous solution of ferrous sulfate heptahydrate to the aqueous solution of cobalt chloride hexahydrate is 1:0.2-0.

7.

5. The EMI shielding and absorbing material according to claim 2, characterized in that, In the mixed solution of NaBH4 and potassium hydroxide, the mass concentration of NaBH4 is 3.8-7.5 g / L and the mass concentration of potassium hydroxide is 0.6-1.0 g / L.

6. The EMI shielding and absorbing material according to claim 1, characterized in that, The preparation process of the mesoporous titanium dioxide includes the following steps: hydrated titanium dioxide and potassium carbonate are dissolved in water at a molar ratio of 2:1-1.3 to form a non-flowing slurry, which is coated onto a thin ceramic sheet and dried. Then, the slurry is heated to 800-900℃ in a muffle furnace and held at that temperature for 2-3 hours, followed by slow cooling to room temperature. The resulting whiskers are ultrasonically dispersed in distilled water, filtered, and dried. Distilled water is added again to keep the mixture moist, and the mixture is allowed to stand at room temperature for 7 days. The mixture is then stirred in 1 mol / L hydrochloric acid, filtered, washed, and dried. The resulting crystals are then heat-treated in a muffle furnace at 300-500℃ to obtain the mesoporous titanium dioxide.

7. The EMI shielding and absorbing material according to claim 1, characterized in that, The alkenylsiloxane is at least one of allyltrimethoxysilane, 3-methyl-allyltrimethoxysilane, bis(trimethoxysilylmethyl)ethylene, 1,4-trimethoxysilyl-2,3-butene, allyltriethoxysilane, 2-methyl-allyltripropoxysilane, 3-methyl-allyltripropoxysilane, 2-methyl-2-enbutyltripropoxysilane, allyltripropoxysilane, 2-enbutyltrimethoxysilane, and 2-enbutyltriethoxysilane.

8. A method for preparing the EMI shielding absorbing material according to any one of claims 1-7, characterized in that, Includes the following steps: S1: The iron-cobalt alloy nanoparticles are dispersed in ethanol and diluted with dichloromethane, then cast onto a glass plate. After evaporation and drying, a glass plate containing an iron-cobalt nano-alloy layer is formed. S2: Mesoporous titanium dioxide and alkenyl siloxane are completely dispersed in THF to obtain a mixed solution with a mass fraction of 15-16 wt%. This solution is poured into a petri dish containing an iron-cobalt nano-alloy layer obtained in S1, allowing the mixed solution to penetrate into the iron-cobalt nano-alloy layer mesh. Then, 1 mol / L hydrochloric acid solution is added dropwise, and the mixture is heated at 40-50℃ for 3-5 hours. After rinsing and drying, the film is peeled off from the glass plate and placed in a vacuum oven at 150℃ for high-temperature annealing for 1-2 hours to obtain the EMI shielding and absorbing material.

9. The method for preparing the EMI shielding absorbing material according to claim 8, characterized in that, The mass ratio of the mesoporous titanium dioxide and alkenyl siloxane in S2 is 0.5-0.8:

1.

10. The application of the EMI shielding and absorbing material according to any one of claims 1-7, characterized in that, In the preparation of the EMI shielding and absorbing material, the glass plate is replaced with a PET film.